International Law in Crisis: Reaffirming the Rule of Law in a Divided World - Morais, Herbert V (Journal of Malaysian and Comparative Law, 2019)
This is a reproduction in its original form (except for slight editorial change) of the Inaugural Lecture delivered by Professor Dr Herbert V Morais at the Faculty of Law of the University of Malaya, Kuala Lumpur, Malaysia, on 9 October 2007.